Low Temperature Storage Stimulates Fruit Softening and Sugar Accumulation Without Ethylene and Aroma Volatile Production in Kiwifruit - Mitalo, Oscar W.; Tokiwa, Sumire; Kondo, Yuki; Otsuki, Takumi; Galis, Ivan; Suezawa, Katsuhiko; Kataoka, Ikuo; Doan, Anh T.; Nakano, Ryohei; Ushijima, Koichiro; Kubo, Yasutaka (Frontiers in Plant Science, 2019)
Fruit ripening in response to propylene (an ethylene analogue), 1-methylcyclopropene (1-MCP, an ethylene action inhibitor) and low temperature (5ºC) treatments was characterized in ‘Kosui’ kiwifruit (Actinidia rufa A. chinensis). Propylene treatment induced ethylene production, with increased expression levels of 1-aminocyclopropane-1-carboxylic acid (ACC) synthase 1 (AcACS1) and ACC oxidase 2 (AcACO2), and rapid fruit softening together with increased expression levels of polygalacturonase (AcPG) and expansin 1 (AcEXP1) within 5 d. Fruit soluble solids concentration (SSC) and contents of sucrose, glucose, and fructose together with the expression levels of -amylase 1 (Ac-AMY1), Ac-AMY2 and invertase (AcINV3-1) increased rapidly after 5 d exposure to propylene. Furthermore, propylene exposure for 5 d was sufficient to induce the production of key aroma volatile compounds, ethyl- and methyl butanoate, accompanied with increased expression levels of alcohol acyl transferase (AcAAT). Application of 1-MCP at the start of the experiment, followed by continuous exposure to propylene, significantly delayed fruit softening, changes in SSC and sugars, and strongly suppressed the production of ethylene, aroma volatiles and expression of associated genes. During storage, fruit softening, SSC and sugar increase, and increased expression of genes associated with cell wall modification and carbohydrate metabolism were registered without detectable ethylene production; however, these changes occurred faster at 5ºC compared to 22ºC. Interestingly, ethyl and methyl butanoate as well as AcAAT expression were undetectable in kiwifruit during storage, while they were rescued by post-storage propylene exposure, indicating that the production of aroma volatile compounds is strongly ethylene-dependent. Transcript levels of a NAC-related transcription factor (TF), AcNAC3, increased in response to both propylene and low temperature treatments, while AcNAC5 was exclusively up-regulated by propylene. By contrast, transcript levels of a MADS-box TF, AcMADS2, exclusively increased in response to low temperature. The above findings indicate that kiwifruit ripening is inducible by either ethylene or low temperature signals. However, fruit ripened by low temperature were deficient in ethylene-dependent aroma volatiles, suggesting that ethylene signaling is non-functional during low temperature-modulated ripening in kiwifruit. These data provide further evidence that ethylene-dependent and low temperature-modulated ripening in kiwifruit involve different regulatory mechanisms.